2008
DOI: 10.1007/s11244-008-9106-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Phase-Pure M1 MoVTeNb Oxide Catalysts by Hydrothermal Synthesis—Influence of Reaction Parameters on Structure and Morphology

Abstract: This work presents a detailed investigation of the preparation of MoVTeNbO x catalysts by hydrothermal synthesis. Phase-pure synthesis of M1 has been achieved applying the metals in a molar ratio Mo/V/Te/Nb = 1/0.25/ 0.23/0.12. Raman, UV/Vis spectroscopy, and SEM/EDX analysis show that the elements are inhomogeneously distributed in the initial suspension that is formed after mixing the metal salts in an aqueous medium. Iso-and heteropoly anions of molybdenum, free telluric acid as well as supramolecular polyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 43 publications
1
27
0
1
Order By: Relevance
“…These particles spontaneously interlocked, thus generating a highly aggregated microstructure of HT-M1. [32,33,35] Heat activation of the H 2 O 2 -washed powder does not lead to any significant changes in the phase composition; the as-prepared W-M1 catalyst is single-phase M1 (Figure 4 A). Higher magnification images of this product clearly reveal the multistep structuring of the lateral surface of the cylindrical particles and a flat termination of the basal planes (inset in Figure S1B The XRD patterns for the hydrothermally derived catalyst crystallized through annealing at 873 K in Ar for 2 h prove the phase-purity of the HT-M1 catalyst (Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These particles spontaneously interlocked, thus generating a highly aggregated microstructure of HT-M1. [32,33,35] Heat activation of the H 2 O 2 -washed powder does not lead to any significant changes in the phase composition; the as-prepared W-M1 catalyst is single-phase M1 (Figure 4 A). Higher magnification images of this product clearly reveal the multistep structuring of the lateral surface of the cylindrical particles and a flat termination of the basal planes (inset in Figure S1B The XRD patterns for the hydrothermally derived catalyst crystallized through annealing at 873 K in Ar for 2 h prove the phase-purity of the HT-M1 catalyst (Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the catalytic relevance of the crystallographic (001) planes (basal planes of elongated M1 particles) has been intensively discussed in the literature. [6,16,[28][29][30][31][32][33][34][35] Subsequent annealing in an inert atmosphere is necessary to crystallize the solids and to derive balanced oxidation states of the key elements. The situation is further complicated by the facts that the M1 phase is only accessible in a certain compositional range and that the surface composition of the active catalyst is extremely sensitive towards operation conditions.…”
mentioning
confidence: 99%
“…The hydrothermal synthesis of MoVTeNb oxide nanoparticles (M1 phase) illustrates the high degree of selectivity that can be achieved through a carefully tuned hydrothermal process. [68] After a multitude of parameter optimizations, for example, of the reaction time, the temperature, the reactor inlay, and the stirring mode, XANES/ EXAFS studies demonstrated that the hydrothermal reaction is the crucial step leading to a homogeneous mixed-oxide phase with all five cations incorporated. Post-treatment at 550 8C then affords a crystalline product for catalytic applications.…”
Section: Hydro-and Solvothermal Methodsmentioning
confidence: 99%
“…[142] 1,4-Butanediol turned out to be the optimal surface stabilizer during the reaction, because it limits the particle growth and prohibits agglomeration. Finally, the Mo-V-Te-Nb-O system [68] has not only been accessed with hydrothermal and spray-drying methods, [143] but also with microwave irradiation as a heat source. [144] In this case, the MW-approach led to the formation of the M1 phase with an interesting open structure and high catalytic activity.…”
Section: Microwave-assisted Strategiesmentioning
confidence: 99%
“…[142] Die Partikelgröße wurde dabei durch Verwendung von 1,4-Butandiol gesteuert, das durch Oberflächenstabilisierung das Teilchenwachstum beschränkt und Agglomerationsphänomene verhindert. Auch das Mo-V-Te-Nb-O-Oxidsystem [68] wurde nicht nur mit Hydrothermal-und Spraytrocknungsmethoden [143] erschlossen, sondern auch mit Mikrowellenstrahlung als Heizquelle. [144] Diese Strategie führte schließlich zur Bildung der M1-Phase dieses Systems mit einem interessanten offenen Strukturmotiv und hoher katalytischer Aktivität.…”
Section: Mikrowellensynthesenunclassified